2022
DOI: 10.1002/jev2.12186
|View full text |Cite
|
Sign up to set email alerts
|

Highly‐metastatic colorectal cancer cell released miR‐181a‐5p‐rich extracellular vesicles promote liver metastasis by activating hepatic stellate cells and remodelling the tumour microenvironment

Abstract: Liver metastasis of colorectal cancer (CRLM) is the most common cause of CRC‐related mortality, and is typically caused by interactions between CRC cells and the tumour microenvironment (TME) in the liver. However, the molecular mechanisms underlying the crosstalk between tumour‐derived extracellular vesicle (EV) miRNAs and the TME in CRLM have yet to be fully elucidated. The present study demonstrated that highly metastatic CRC cells released more miR‐181a‐5p‐rich EVs than cells which exhibit a low metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 31 publications
1
85
0
Order By: Relevance
“…According to the diverse components, TME is widely accepted to be classified into three subtypes: immune-desert, immune-inflamed, and immuneexcluded (39). With more and more focus on TME, researchers have found that TME is closely associated with the p r o g n o s i s o f m u l t i p l e t u m o r s a n d r e s p o n s e t o chemoradiotherapy and immunotherapy, such as colorectal cancer, melanoma, gastric cancer, and intrahepatic cholangiocarcinoma (40)(41)(42)(43)(44). In colorectal cancer, the high level of infiltrated cytotoxic CD8 + T cells at the center or margin of the tumor predicts a low risk of recurrence at 5 years (45).…”
Section: Introductionmentioning
confidence: 99%
“…According to the diverse components, TME is widely accepted to be classified into three subtypes: immune-desert, immune-inflamed, and immuneexcluded (39). With more and more focus on TME, researchers have found that TME is closely associated with the p r o g n o s i s o f m u l t i p l e t u m o r s a n d r e s p o n s e t o chemoradiotherapy and immunotherapy, such as colorectal cancer, melanoma, gastric cancer, and intrahepatic cholangiocarcinoma (40)(41)(42)(43)(44). In colorectal cancer, the high level of infiltrated cytotoxic CD8 + T cells at the center or margin of the tumor predicts a low risk of recurrence at 5 years (45).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, substantial efforts that target HSCs have been made for the treatment of liver fibrosis that show promising results. 41,42 bFGF exerts antifibrotic effect in chronic liver injury. While the underlying mechanism of bFGF-mediated regulation of liver fibrosis is not completely clear, different bFGF-related signaling pathways have been discovered, including the c-Jun N-terminal kinase (JNK), mitogen-activated protein kinase (MAPK), extracellular signal-regulated kinase (ERK), and Janus kinase (JAK) pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhao et al demonstrated that HSCs could communicate back with the primary tumor following activation by miR-181a-5p released from CRC cells. Following EV uptake, HSCs facilitated CRC cell migration, invasion, and metastasis formation by increasing expression of α-SMA and fibronectin in the liver ECM while reducing vitronectin and tenascin C. Moreover, they also secreted CCL20 into circulation, which upregulated further miR-181a-5p production by primary tumor cells in a positive feedback loop [ 25 ]. This cross-communication between the PMN and the primary tumor expands past the notion of unidirectional signaling and offers additional targets for therapeutic blockade.…”
Section: Liver Componentsmentioning
confidence: 99%